Preference and performance of the rice leaf folder, Cnaphalocrocis medinalis, in relation to rice developmental stage. Issue 8 (16th March 2021) - Liu, Huan; Han, Yongqiang; Zhong, Yuqi; Ali, Asad; Hou, Maolin
Abstract: The relationship between oviposition preference and offspring performance is critical to an understanding of the interaction between herbivores and host plants. Although the topic has been addressed widely in plant species‐herbivore systems, it has rarely been investigated in plant stage‐herbivore systems. In this study, we evaluated oviposition preference and offspring performance of the rice leaf folder (RLF), Cnaphalocrocis medinalis (Guenée) (Lepidoptera: Pyralidae), on rice plants at the seedling (SS), tillering (TS), and booting (BS) stages. In preference assays, females deposited more eggs on TS and BS than on SS plants in cage tests, and preferred TS and BS odors over SS odors in Y‐tube olfactometer tests. Offspring performance was affected by plant stage. The RLF offspring performed well when the larvae fed on BS leaves, as indicated by the highest larval survival and pupation rate and the greatest adult longevity. RLF offspring performed also well when the larvae fed on TS leaves, where fecundity was the highest. The high RLF offspring performance on TS and BS plants coincided with high larval consumption of TS and BS leaf mass relative to SS leaf mass. Our findings confirm the prediction of the preference–performance hypothesis. The results explain the pest damage patterns in mixed croppings of one‐ and two‐season rice and are of significance for management of the pest through synchronization of rice planting. Abstract : By employing behavioral, feeding, and offspring performance assays, we showed that Cnaphalocrocis medinalis (Lepidoptera: Pyralidae) performed better on leaves at tillering and booting stages than on leaves at seedling stage, and the females preferred tillering and booting plant odors over seedling plant odors, confirming the prediction of the preference–performance hypothesis. These results explain the pest damage patterns in mixed cropping of one‐ and two‐season rice and are of significance for management of the pest through synchronizing rice planting.